Em novos territórios: um olhar sobre a migração venezuelana em Foz do Iguaçu - Bello, Paola Bernardon (2021)
This dissertation presents an ethnographic observation of part of the Venezuelan migrant population that is currently in Foz do Iguaçu (PR). It seeks to assess the importance of access to information and the establishment of support networks so that Venezuelan migrants are able to guarantee the respect and fulfillment of their rights in Brazil and, thus, be less exposed to vulnerabilities. Based on this scenario, it aims to address the different vulnerabilities in which migrants may find themselves in the country, depending on the support networks they have established in the new territory and the level of reliability of the information on migration and rights to which they have access. For conceptions about migration, refuge and vulnerabilities, the text makes use of current legislation (Migration Law, the Refugee Statute, Cartagena Declaration) and documents produced by United Nations agencies. The dissertation also uses Clifford's (2011) theories on ethnography; Machado, Jung and Pires-Santos (2019); Mattos (2011); Maliguetti (2004); and Peirano (2014). On culture, it quotes Wagner (2010) and on cultural relations, Canclini (1998). It also highlights theorists such as Wortham (2001) and Silvermann (2009) to make connections about narratives. And it resorts Raffestin (1993), on territorialization, Cardin (2018) for reflections on migrations and networks, and Barth (1969), Santos (2000) and Saquet (2005) on territory and power relations. The research also uses ethnographic observation to listen to the life stories of six people who migrated to Foz do Iguaçu at different times and in different situations. Thus, the narratives seek to highlight the main demands so that they can find conditions worthy of survival and restarting their trajectories.